Effect of polysaccharide concentration on heat-induced Tremella fuciformis polysaccharide-soy protein isolation gels: Gel properties and interactions - Zhao, Yingting; Wang, Danni; Xu, Jingxin; Tu, Dongkun; Zhuang, Weijing; Tian, Yuting (International journal of biological macromolecules, 2024)
The formation of a single soybean protein isolate (SPI) gel is limited by the processing conditions, and has the disadvantages of poor gel property, and it is usually necessary to add other biomacromolecules to improve its property. In this study, we investigated the effects of polysaccharide concentration on gel properties and interaction mechanisms of Tremella fuciformis polysaccharide (TFP)-SPI complexes. It was found that (1) the rheological properties, texture properties, water-holding properties, and thermal stability of TFP-SPI composite gels were improved with the addition of TFP (0.25–2.0 %, w/v) in a concentration-dependent manner; (2) hydrogen bond, the electrostatic interaction, hydrophobic interaction, and disulfide bond in the gel system increased with the increase of TFP concentration; (3) the electrostatic and hydrophobic interactions played an important role in the formation of the TFP-SPI composite gel while hydrogen bond formation was the least contributor to the binary composite gel network. Overall, TFP is not only a critical health food but also a promising structural component for improving the gel properties of SPI. [Display omitted]